Hubungan Pengetahuan, Kepatuhan dan Ukuran LILA dengan Status Anemia Ibu Hamil Pasca Pendampingan Tim Pendamping Keluarga - Christina Pernatun Kismoyo; Mela Kurnia Agustin; Era Revika (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Anemia in pregnant women is a significant health issue in various countries, including Indonesia. This condition can increase the risk of preterm birth, low birth weight babies, and complications during delivery. The prevalence of anemia in pregnant women in Yogyakarta was 16.50% in 2022, with Bantul district ranking third highest. In Panggungharjo Village, Bantul, anemia in pregnant women has become a focus in efforts to improve maternal and child health.Objectives:To identify three factors influencing the anemia status of pregnant women after assistance from the Family Assistance Team.Methods:This research is a quantitative study with an analytical observational design and a cross-sectional approach. The sample consisted of 78 respondents from a population of 352 pregnant women in Panggungharjo Village. The variables studied were knowledge of anemia, adherence to iron tablet consumption, Upper Arm Circumference (LILA), and hemoglobin (Hb) levels. Data were collected through questionnaires and analyzed using SPSS version 22.Results:The study found that knowledge about anemia and adherence to consuming iron tablets did not have a significant relationship with anemia status. However, Upper Arm Circumference (LILA) had a significant relationship with anemia status (ρ = 0,013). Pregnant women with normal LILA tended to have better anemia status compared to those experiencing Chronic Energy Deficiency (KEK).Conclusion: Upper Arm Circumference (LILA) is the most significant factor influencing anemia status in pregnant women. Efforts to improve the nutritional status of pregnant women through interventions that increase LILA can be an effective strategy to reduce the prevalence of anemia. The Family Assistance Team is advised to continue providing education about anemia and the importance of consuming iron tablets, as well as to monitor the nutritional status of pregnant women holistically and continuously.Keywords: Anemia, pregnant women, family assistance